Bringing in the externalities: historians, time work and history's boundaries. Issue 2 (2nd April 2020) - Kramer, Paul A.
Abstract: This article responds to the pieces in this forum, bridging them through the concept of history's externalities. What have historical actors identified as outside their spheres of analysis and concern, and what do they place on the inside? Similarly, what do historians place outside and inside the boundaries of their scholarship? And where, along the borders between academia and other spaces of knowledge production, should advanced training in history occur? The article argues for the benefits of mapping these different relationships between inside and outside and, in each instance, for the advantages of bringing the externalities 'in'. It also reflects on the stakes for historians of identifying the present moment as one of urgency or emergency.